Characterisation of Hepatitis C Virus antiviral resistance in the era of direct acting antivirals - Smith, D (2019)
Hepatitis C Virus infects an estimated 71 million people world wide and accounts for approxi- mately 399,000 deaths per year from end stage liver failure due to cirrhosis or hepatocellular carcinoma. The development of direct acting antivirals (DAAs) has led to the elimination of the HCV infection, known as a sustained viral response (SVR) in >95% of patients who are treated. However, resistance associated substitutions (RAS) have been described for all DAAs and the presence of these RAS have been shown by multiple studies to reduce SVR rates. The aim of this work is to better characterise HCV RAS by studying the natural prevalence of RAS in a treatment naive cohort, to identify novel RAS and to study the prevalence of RAS in a cohort of patients who had not been successfully cured using first line DAA therapy and their effect on subsequent re-treatment. RAS to NS5A inhibitors in treatment naive genotype 3 (gt3) HCV infected patients are common with ∼12% of patients in a treatment naive cohort having detectable RAS. All gt3b and gt3g viruses had the A30K + L31M RAS combination, which was shown to dramatically increase the EC50 of NS5A inhibitors. Using viral genome wide association studies and whole genome HCV sequences the novel amino acid substitutions in NS2 I132V, NS2 119A NS3 67V and NS5B A150V were identified as being associated with sofosbuvir treatment failure in HCV gt3a infection. SVR rates for the retreatment of patients with prior failure to direct acting antiviral therapy are high (>89%), despite RAS being present in 71% of patients. However, the SVR rate for gt3 infected patients is significantly lower only 81%. This work demonstrates that despite SVR rates of >95% with DAA therapy, both innate resistance of understudied HCV subtypes and RAS present in treatment naive and experi- enced patients can effect treatment outcomes and should be viewed with concern particularly in patients who fail first-line therapy.